RETRACTED: An Innovative Mobile Application for Analyzing Learning Objectives using Bloom's Taxonomy - Hamada, Samir; AlShibli, Mohammad; Hamada, Salwa (Trends in Computer Science and Information Technology, 2025)
Nowadays most learning institutions use Bloom’s Taxonomy to measure the student's understanding levels and to determine their understanding levels of the learning materials, as well as instructional strategies that will enable them to complete the activities successfully. In this paper, we are proposing an innovative mobile application for analyzing learning objectives using Bloom's Taxonomy, which can facilitate the use of Bloom’s taxonomy and provide substantial help for educators.